Isolation and characterization of Newcastle disease virus subgenotype VII.2/VIIi from commercial chicken and swan in Malaysia - Mahamud, Siti Nor Azizah; Sheau, Wei Tan; Youn, So Youn; Lee, Hyun Jeong; Lee, Ji Youn; Kwon, Young Kuk; Ideris, Aini; Omar, Abdul Rahman (Universiti Putra Malaysia Press, 2021)
Frequent Newcastle disease (ND) outbreaks in poultry have been reported in Southeast Asia, including Malaysia. However, limited studies have been carried out on detecting the Newcastle disease virus (NDV) from non-poultry birds. In this study, the detections of NDV were carried out using tissues samples from suspected ND cases from commercial chickens and swab samples of non-poultry birds captured in bird sanctuaries. Five samples from commercial chickens and one sample from black swans were found positive for ND. They were classified as velogenic NDV based on the partial sequencing of the fusion (F) gene, which revealed the amino acid motif on the F cleavage site of 112RRQKRF117. In addition, phylogenetic analysis based on partial F gene showed that all NVD isolates are classified as class II genotype VII subgenotype VII.2 (VIIi) and are clustered together with NDVs isolated from chickens in 2017 in Indonesia. This finding indicates the occurrence of subgenotype VII.2 (VIIi) as the fifth panzootic of ND in Malaysia and the importance of the epidemiology of virulent NDV in various avian species.